Re-branding Malaysian SME food products for global marketing using enhanced packaging strategies / Ghazali Daimin - Daimin, Ghazali (2010)
The forces of globalisation in the business world today had pushed the local Small and Medium-sized Entrepreneurs (SMEs) in Malaysia to change their business mechanism and strategies in order to penetrate the global market. In view of the fact that business and business strategy now has becoming more dynamic and competitive especially at international level, the Small and Medium-sized Entrepreneurs (SMEs) in Malaysia are in dire need of an exclusive approach in the form of creative strategy to support their businesses to expand internationally. This research is an attempt to gain a better understanding of how the elements of re-branding can be used as a tool to increase marketability of Malaysian SME food products upon competing further in international market. Recognizing the importance of re-branding process' for Malaysian SMEs, this research paper focus specifically on encouraging enhanced packaging strategies by having a distinctive and creative food packaging design specifically focused towards micro-sized entrepreneur. Review of past literature of this research relied upon textual material and archival data from selected journal and proceedings, magazines and Exporter's Encyclopaedia. For detailed analysis at the subject, a qualitative method has been employed throughout this research. The implementation of qualitative methodology paradigms; in-depth interviews has largely contributed towards completion of this study. All in all, the researcher managed to complete Seven (7) Chapters of this research with strong justification, recommendation and findings. The conclusion from the result of conducting this research is considered sufficient to indicate that the research questions formed earlier is robustly answered. The researcher has discussed and shown the suggested packaging design for Malaysian SMEs together with the right components and technical specifications that should be followed that is rightfully fit to compete in the international market. Exclusivity and design practicality of the packaging has been identified by the researcher as the right strategy for food product together with the product's own delectability. Finally, the researcher believed that the quality of food, smart marketing and enhanced packaging strategy is the real key of success for Malaysian SMEs for food products at the global market scene.